Food information presentation: consumer preferences when eating out. Issue 8 (5th August 2019) - Bray, Jeff; Hartwell, Heather; Price, Sarah; Viglia, Giampaolo; Kapuściński, Grzegorz; Appleton, Katherine; Saulais, Laure; Perez-Cueto, Federico J.A.; Mavridis, Ioannis
Abstract : Purpose: Advances have been made in the provision of nutritional and ingredient information on packaged food, however, there is a need to translate this to eating out reflecting consumer desire for greater transparency and knowledge of menu content. The purpose of this paper is to assess consumer's preferences for food information presentation in four European countries (UK, Greece, Denmark and France) in a workplace dining setting. Design/methodology/approach: This study focusses on workplace canteens since the regularity in which they are used provides an important context and potential for behaviour change. An exploratory phase designed iteratively in collaboration with experts, end-users and researchers (qualitative) informed a survey (quantitative) conducted in four European countries. The survey was used to examine workplace diners' preferences towards food information presentation. Findings: Differences were found and clustered ( n =5) to "heuristic processors" (33 per cent) "brand orientated" (25 per cent) "systematic processors" (17.3 per cent) "independent processors" (16.1 per cent) and "tech-savvy" (8.6 per cent). Dual-process theories were used to analyse the findings and produce new insight into how menu information can be most effectively delivered. Originality/value: When eating-out consumers struggle to make choices or make the wrong choice from a health perspective, partly caused by a lack of nutrient profile information as well as other criteria of concern. Giving catering managers the understanding of preferred communication channels can enable a more competitive operator. Traffic light labelling was the optimal presentation with the opportunity for consumers to discover more detailed information if desired. For the first time this research has given operational clarity whilst allowing food providers to be considered as part of corporate health.